(untitled) (Proceedings of the International Conference on Education, 2021)
The way in which entrepreneurship is taught has a high impact on students’ entrepreneurial capacity. In this sense, there have been several studies that analyze the impact that different forms of teaching have on the development of entrepreneurship skills. Different research indicates, in a general sense, that the more education concerning entrepreneurship, the more entrepreneurship skills are developed. Other studies report that students that were involved in a more practical and reflective educational model, reported greater intentions of undertaking an entrepreneurial experience. However, none of these studies use the development of “case studies” as a means of developing entrepreneurship skills. In this sense, this research project proposes an experimental study, with a control group of 30 students and three intervention groups of 90 students (from fifth semester forward), in order to measure the impact that the development of real entrepreneurs case studies (either of success or failure) had on students. All of this, in order to improve the attitudinal competencies of: (i) problem analysis mentality before proposing early solutions, ii) mentality of testing low-cost solutions before investing, and (iii) data-driven decision-making mentality rather than intuition. Results suggest that there were noticeable improvements in the soft skills learned by the students. There was a percentage change in the results of the intervention groups in comparison with the control group (even when the control group also registered improvements). Further studies may test this intervention in different settings or measure other soft/hard skills using the same intervention.